Biological and anti-inflammatory evaluation of two thiazole compounds in RAW cell line - Faour, Wissam (2012)
The anti-inflammatory effect of two new thiazoles derivatives CX-32 (N-[4-(4-hydroxy-3-methoxyphenyl)-1,3-thiazol-2-yl]acetamide ) and CX-35 (4-(2-amino-1,3-thiazol-4-yl)-2-methoxyphenol), was investigated in LPS-stimulated RAW 264.7 cell line. Synthesis, structure analysis and purity of these compounds were evaluated by high performance liquid chromatography, H1 NMR, and C13 NMR. Assessment of CX-32 and CX-35 inhibitory effect on cyclooxygenase-2 (COX-2) activity was achieved by incubating LPS-activated RAW cells with 25 μM, 50μM or 100μM of CX-32 or CX-35 respectively. Levels of secreted PGE2 were evaluated by enzyme immunoassay (EIA) and levels of COX-2 protein were measured by western blot. Finally, cell viability experiments were undertaken to assess the toxicity of each compound. Treatment of LPS-activated RAW cells with 25 μM, 50 μM, or 100 μM of CX-35 or CX-32 respectively, prevented the production of prostaglandins, but was without effect on COX-2 protein levels. Moreover, CX-35 and CX-32 reduced PGE2 production to levels comparable to those obtained in LPS-activated RAW cells incubated with the selective COX-2 inhibitor NS 398. Furthermore, both CX-32 and CX-35 showed no toxic effects, since viability of non-treated Hela cells was similar to Hela cells incubated with either CX-35 or CX-32. Our data demonstrated that CX-32 and CX-35 significantly blocked prostaglandin production induced during inflammatory cellular stress, possibly acting through specific COX-2 inhibition; confirmation of this hypothesis requires further investigation.